Color-tunable upconversion luminescence and prolonged Eu3+ fluorescence lifetime in fluoride KCdF3:Yb3+, Mn2+, Eu3+via controllable and efficient energy transfer. Issue 29 (20th May 2020) - Han, Xinxin; Song, Enhai; Chen, Weibin; Zhou, Yayun; Zhang, Qinyuan
Abstract : Intense Eu 3+ upconversion emission is realized in KCdF3 :Yb 3+, Mn 2+, Eu 3+ via controllable and efficient unidirectional energy transfer from Yb 3+ -Mn 2+ dimers. Moreover, significantly prolonged Eu 3+ UC emission lifetime is observed in this system. Abstract : Due to the lack of intermediate levels and the large energy mismatch with Yb 3+, the achievement of efficient upconversion (UC) of Eu 3+ is a great challenge. Herein, intense UC emission of Eu 3+ is demonstrated via controllable and efficient unidirectional energy transfer from Yb 3+ –Mn 2+ dimers in perovskite fluoride KCdF3 :Yb 3+, Mn 2+, Eu 3+ synthesized by a facile solvothermal method. The UC emission color of KCdF3 :Yb 3+, Mn 2+, Eu 3+ can be well tuned from yellow to orange and ultimately turned into Eu 3+ pure red emission by controlling the Eu 3+ concentration. Moreover, a significantly prolonged Eu 3+ UC emission lifetime is observed in this system, and it is ascribed to the genetic effect of the sustained resonance energy transfer from Yb 3+ –Mn 2+ dimers to Eu 3+ . The pump power and temperature dependent UC behaviors further suggest that the phosphor exhibits excellent chromaticity stability. Owing to the long-lived and chromaticity stable UC luminescence, the as-prepared KCdF3 :Yb 3+, Mn 2+, Eu 3+ phosphor may be a highly suitable candidate for lifetime-encoded information encryption, anti-counterfeiting, etc.